The Psychological Characteristics of People with High and Low Levels of Professional Well-Being - Baranauskienė, Ingrida; Kovalenko, Alla; Pakhol, Borys (Social Welfare: Interdisciplinary Approach, 2024)
The article presents a comparative analysis of the psychological characteristics of people having high and low levels of professional well-being. There were significant differences for all studied indicators between groups with high and low professional well-being. The widest differences between the two groups were found for average values of professional commitment, job satisfaction, autonomous motivation, in-demand profession, and professional psychological well-being; the smallest differences were determined for average values of life satisfaction, climate in a team and controlled motivation. Significant differences depending on a level of professional well-being were revealed and professional well-being correlations with the studied indicators in groups with its high and low levels were analyzed. A high level of professional well-being correlated strongly with many indicators of professional work: professional commitment, in demand in profession, psychological capital, professional self-attitude, meaningfulness of life, job satisfaction, professional psychological well-being, autonomous motivation and climate in a team. A low level of professional well-being correlated with the examined indicators with medium to weak strength. This confirms the integral nature of the phenomenon of professional well-being. The regression models for factors of high and low levels of professional well-being were similar. In both groups, the most important factors of professional well-being were: professional commitment, in demand in profession, climate in a team, subjective social well-being and meaningfulness of life. The differences were revealed only for the signs of coefficients applied to subjective social well-being and meaningfulness of life.